La promotion du mieux-être par l’activité physique en milieu minoritaire: l’Institut de leadership de l’Université de Moncton, 1969-1989 - Forbes, Marie-Line; Kennedy, Greogry; Zaiane-Ghalia, Selma (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2016)
This article examines the creation and early history of the Institute of Leadership of the Université de Moncton, which was composed of the professors of the Department of Physical Education. The institute was a unique project that aimed to serve the minority Acadian population of the Atlantic Provinces through the promotion of sports, recreation, and health in French. It evolved from a focus on the training of elite athletes, coaches, and referees to a specialization in research and the development of school curricula and municipal plans aimed at the entire population. The evolution of the institute reflected both Canadian trends in sports programs and the particular circumstances of collective action and nationalism in Acadia.